HUBUNGAN HASIL BELAJAR KEWIRAUSAHAAN DAN PENGALAMAN PRAKTIK KERJA LAPANGAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK KELAS XII KOMPETENSI KEAHLIAN OTOMOTIF - Ilham Rizqi Aminudin; Jumhur, Aam Amaningsih; Avanti, Ratu Amalia (Jurnal Pendidikan Teknik dan Vokasional, 2021)
This study aims to determine the relationship between the learning outcomes of entrepreneurship and job training experience with a class XII student interest in entrepreneurship competence automotive expertise SMK X. This research method is correlation method. The population in this study is a class XII student competence automotive expertise SMK North Jakarta area as many as 4,461 students in 2019/2020, SMK 55, SMK 56, SMK 4, and SMK 36. The sampling technique used purposive sampling to determine the size of the sample using the formula Slovin and data analysis technique used is simple regression analysis and correlation. The results of this study were (1) the results of entrepreneurial learning has a positive and significant relationship to the interest in entrepreneurship class at SMK XII North Jakarta area with r1 values of 0.181 and a r2 by 3,2%. (2) Experience job training has a positive and significant relationship to the interest in entrepreneurship class XII at SMK Region North Jakarta with a value of r2 0,452 and a r2 by 20,3% (3) the results of study entrepreneurship and practical experience of field work jointly have a positive influence and significantly to class XII student interest in entrepreneurship at SMK North Jakarta area with values of 0.479 and r3 r2 result by 23%. Keywords: Quantitative Associative, Relationship Research, Interest In Entrepreneurship